1993
DOI: 10.1042/bj2950031
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of insulin secretion from normal rat islets by inhibitors of the post-translational modifications of GTP-binding proteins

Abstract: Many GTP-binding proteins (GBPs) are modified by mevalonic acid (MVA)-dependent isoprenylation, carboxyl methylation or palmitoylation. The effects of inhibitors of these processes on insulin release were studied. Intact pancreatic islets were shown to synthesize and metabolize MVA and to prenylate several candidate proteins. Culture with lovastatin (to inhibit synthesis of endogenous MVA) caused the accumulation in the cytosol of low-M(r) GBPs (labelled by the [alpha-32P]GTP overlay technique), suggesting a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
155
0
4

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(174 citation statements)
references
References 85 publications
15
155
0
4
Order By: Relevance
“…Pourquoi n'y a-t-il pas alors plus d'exemples citant l'efficacité des statines dans la prévention du DT2 ? Trois études indépendantes ont montré qu'un traitement d'îlots isolés de rat ou de cellules MIN-6 par des statines lipophiles (simvastatine, atorvastatine et lovastatine) est toxique sur la cellule , alors que la pravastatine, hydrophile, est sans effet [28][29][30]. Des études interventionnelles chez l'homme, ciblant spécifiquement le rôle des statines sur la fonction  cellulaire, seront nécessaires pour déterminer la nature exacte de ce lien.…”
Section: Quelle Pertinence Chez L'homme ?unclassified
“…Pourquoi n'y a-t-il pas alors plus d'exemples citant l'efficacité des statines dans la prévention du DT2 ? Trois études indépendantes ont montré qu'un traitement d'îlots isolés de rat ou de cellules MIN-6 par des statines lipophiles (simvastatine, atorvastatine et lovastatine) est toxique sur la cellule , alors que la pravastatine, hydrophile, est sans effet [28][29][30]. Des études interventionnelles chez l'homme, ciblant spécifiquement le rôle des statines sur la fonction  cellulaire, seront nécessaires pour déterminer la nature exacte de ce lien.…”
Section: Quelle Pertinence Chez L'homme ?unclassified
“…Carboxymethylation is implicated in cell activation [1,[7][8][9]11,13,30,31] and GTP[S], the non-hydrolysable analogue of guanosine triphosphate, stimulates the methylation of some small G-proteins [1,3,13]. Therefore the possibility that this enzyme was regulated by GTP or by a signalling pathway such as Ca# + , cAMP or a protein-kinase-C-mediated process was examined.…”
Section: Regulation In Vitromentioning
confidence: 99%
“…It has been reported that carboxymethylation is involved in the activation of platelets, neutrophils and macrophages [1,7,11] as well as that of normal pancreatic rat islets [13,14] and a pancreatic β-cell line [8]. It is also implicated in the regulation of intracellular pH homeostasis [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No detectable inhibition of Ins(1,4,5)P $ F-stimulated Ca# + inflow was observed when oocytes were preincubated for : 27 h with pertussis toxin, which ADP-ribosylates G i , G o and G t (transducin) [35] ; 24 h with lovastatin, which inhibits the isoprenylation of some monomeric G-proteins [36,37] ; or 5 h with Brefeldin A, an inhibitor of membrane fusion events involving Arf proteins [38] (results not shown). The peptide Arf-1 (2-17), which inhibits the functions of Arf proteins, including the budding of transport vesicles involved in protein trafficking [39], also had no effect on store-activated Ca# + inflow (results not shown).…”
Section: Effects Of Inhibitors and Activators Of G-protein Functionmentioning
confidence: 99%